(untitled) (Chittagong University Journal of Biological Sciences, 2024)
The present study attempted an empirical investigation to the marital adjustment and suicidal ideation of adulthood. In order to collect data, participants were selected purposively; a total 108 respondents were selected. Out of these 108 respondents, 54 were of single family and 54 were of joint family. In the 54 single families, 27 were of rural areas and 27 were of urban areas. And in the 54 joint families, 27 were of rural areas and 27 were of urban areas. Again, each group consisted of 9 early adulthood, 9 middle adulthood and 9 late adulthood. Their age ranges were from 17 to 60 above years. The Bangla version of "Dyadic Adjustment Scale (DAS) (Ilyas 2001)" and "Suicidal ideation scale (Uddin and Hossain 2007)" were used to measure marital adjustment and suicidal ideation. The data were analyzed using mean, standard deviation t-value, one- way analysis of variance (ANOVA) and Pearson product moment correlation. The findings of the present study showed that mean of marital adjustment of late adulthood shows more marital adjustment than middle and early adulthood (F=68.98,df=2,p< 0.00); mean of marital adjustment of joint family was more than single family (F =14.24, df =1, p .< 0.00); mean of marital adjustment of rural areas was more than the urban areas (F = 12.23, df = 1, p < 0.00). On the other hand, early adulthood was more suicidal ideation than middle and late adulthood (F·=. 19.49, df =2, ·p <0.00); single-family was more suicidal ideation than joint family (F = 6.08, df = l, p <0.01); but residence had no significant on suicidal ideation. Result also ’showed negative correlation (r= - 0..32, p<0.001 ) between marital adjustment and suicidal ideation of adults. The Chittagong Univ. J. B. Sci. 8(1&2): 87-98.2013